Estimation of strong motion parameters in the coastal region of gujarat using geotechnical data. Issue 92 (January 2017) - Mohan, Kapil; Rastogi, B.K.; Pancholi, Vasu; Sairam, B.
Abstract: Seven boreholes are drilled in the coastal region of Gujarat; three in Kachchh (at Jangi, Mandvi and Mundra), one in Saurashtra (Jodiya) and three in mainland Gujarat(Dahej, Kamboi and Dholera) to depth of 27–80 m for estimating the surface strong ground motion parameters. These parameters are required for seismic resistant design of structures in the areas. The adopted methodology comprises of three parts: (i) soil modeling and estimation of depth to Engineering Bed Layer (EBL) (a prominent subsurface soil layer with shear wave velocity of 450 m/s to 760 m/s with SPT N value of more than 80) (ii) Estimation of the ground motion at EBL (iii) estimation of ground motion at the surface by 1D ground response analysis using SHAKE program. The soil models are prepared from borehole data and shear wave velocity/ N-values. The ground motion at EBL is estimated using Stochastic Finite Fault source Modeling Technique by considering scenario earthquakes along two major faults of Kachchh (Kachchh Mainland Fault (Mw7.6) and Katrol Hill Fault (Mw7.5)), one of Saurashtra (North Kathiawar Fault (Mw 6.5)) and one of Mainland Gujarat (West Cambay Fault (Mw 6.0)). The surface ground motion is estimated by passing ground motion simulated at EBL through prepared soil models of each site using SHAKE program. The surface peak ground acceleration from 0.076g to 0.396 g and peak spectral acceleration from 0.24g to 1.4 g are estimated at seven coastal sites. Spectral accelerations are found higher than Bureau of Indian Standard (BIS) suggested values at Jangi (between 0.1 and 0.3 s & 0.8–1.4 s), Jodiya (0.1–0.3 s), Mundra (0.3–0.6 s) and Dholera (0.1–0.4 s) sites, where the importance factor of 1.5 needs to be considered. The study suggests taking BIS values at Dahej, Kamboi and Mandvi coastal sites. Highlights: Geotechnical investigations are carried out at seven borehole sites in the coastal, Gujarat on the port sites. The soil modeling is conducted on all seven sites using soil Type, N value and Vs. The scenario earthquakes are considered along major faults to estimate base motion. The surface strong motion parameters are estimated considering soil effect estimated from geotechnical and geophysical parameters.